Product’s Attribute and Consumer Perception in Purchasing Decision: the Case of Young Adult’s Yoghurt Consumption - Yasinta Yudya Saraswati; Mujtahidah Anggriani Ummul Muzayyanah; Endang Sulastri (Buletin Peternakan, 2023)
This research aims to examine the correlation between the attributes and consumer preference for yoghurt. This survey research uses a purposive sampling technique with the criteria age 15-24 years and experiencing to consume yoghurt. Data collection uses an interview approach with a questionnaire as an instrument. A total 257 young adult were selected for this study. The results revealed that consumer perception on yogurt attributes were in "high" categorized with taste, texture, product information, and bottle packaged were preferred to be chosen. Pearson’s R correlation analysis found that all attributes indicate a perfect positive linear relationship with consumer purchasing decisions on yogurt. The attribute that considers the respondents the most is product's information, and the correlation between the attributes and consumer's purchase intention is strongly positive. Thus, market potential and intention to consume yogurt through increasing the value of product attributes need to be assessed.